A manufacturing process for high performance sintered NdFeB magnets

By using an electrophoresis treatment process to coat the anticorrosion coating formed by epoxy resin and special additives on the surface of the sintered NdFeB magnet, the problem of magnetic performance reduction caused by the non-magnetic intergranular phase in the alloying method is solved, and high-performance corrosion resistance and magnetic performance are achieved.

CN118335503BActive Publication Date: 2025-04-18DONGGUAN BAILIBAO MAGNETIC MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410469045.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-18
Publication Date
2025-04-18
Estimated Expiration
2044-04-18

AI Technical Summary

Technical Problem

The existing alloying method improves corrosion resistance by adding alloy elements to neodymium iron boron magnets, but the non-magnetic intergranular phase formed by the alloy elements leads to a decrease in magnetic properties.

Method used

The anticorrosion coating is coated on the surface of the sintered NdFeB magnet by electrophoresis treatment, and the coating formed by epoxy resin and additives (made from nanosilica and 2-amino-5-mercapto-1,3,4-thiadiazole) is improved to improve the corrosion resistance of the magnet.

Benefits of technology

It effectively improves the corrosion resistance and adhesion strength of magnets, avoids the reduction in magnetic properties caused by the addition of alloy elements, and extends the corrosion resistance time of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a manufacturing process of a high-performance sintered NdFeB magnet, and relates to the technical field of permanent magnetic materials. The invention discloses a manufacturing process of a high-performance sintered NdFeB magnet, which comprises the following steps: using a sintered NdFeB magnet as a negative electrode material, placing it in an electrophoresis solution for electrophoresis treatment, coating the surface of the sintered NdFeB magnet with an anti-corrosion coating, and obtaining a high-performance sintered NdFeB magnet; the electrophoresis solution is obtained by mixing epoxy resin, an additive, and distilled water and adjusting the pH to 5-6; the present invention coats the surface of the sintered NdFeB magnet with an anti-corrosion coating to give the magnet excellent corrosion resistance; the anti-corrosion coating prepared in the present invention has high bonding strength and good anti-corrosion effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permanent magnetic materials, and in particular to a manufacturing process of a high-performance sintered NdFeB magnet. Background Art

[0002] Permanent magnetic materials are used as magnetic fields or magnetic force sources, mainly using the magnetic field they generate in the air gap. The larger the maximum magnetic energy product (referred to as magnetic energy product), the larger the magnetic energy field generated in the air gap. Therefore, the larger the magnetic energy product of the permanent magnet, the better. 14 B (2:14:1) main phase, Nd-rich phase (Nd95%, Fe3-5%), B-rich (Nd 1.11 Fe4B4) (1:4:4) phase and a small amount of impurity phase. The Nd-rich phase at the grain boundary accelerates liquid phase sintering and densification. Its composition, structure and distribution also have an important influence on the magnet performance, especially the coercive force. NdFeB magnets have excellent magnetic properties, and the theoretical magnetic energy product reaches 512kJ / m -3 (64MGOe) has become the rare earth permanent magnet material with the highest comprehensive hard magnetic properties and the fastest development since its introduction in 1993, and is called the third generation of rare earth permanent magnet materials. However, this type of magnet is generally formed by powder metallurgy sintering, with a loose structure and high porosity. It is easily corroded when in contact with corrosive media, resulting in poor magnetic stability of the material, and the coercive force is only 1 / 5-1 / 3 of the theoretical value, which hinders the expansion of its application in high-tech fields.

[0003] Alloying is an effective method to reduce the potential difference between the internal phases of the magnet. A large number of studies have shown that alloys that improve the corrosion resistance of sintered NdFeB magnets by alloying can be divided into two categories: (1) M1 (Cu, Ga, Ge, Sn, Zn, Al). Such alloy elements can form Nd-M1 or Nd-Fe-M1 intergranular phases; (2) M2 (Mo, W, Nb, Ti, Zr, V). Such alloy elements will form M2-B, FeM2B intergranular phases, reduce the corrosion electrochemical activity of the intergranular phases inside the magnet, and thus improve the corrosion resistance of the magnet. Studies have also shown that the addition of Dy, Al, Nb, Ga, Ti, W, Mo and other elements can improve the coercive force and temperature stability of the magnet. However, the intergranular phases formed by the addition of alloy elements are all non-magnetic phases, which cannot fundamentally solve the disadvantage of poor corrosion resistance of the magnet. At the same time, with the addition of alloy elements, the magnetic properties (remanence, magnetic energy product) of the magnet will be significantly reduced, and the production cost of the magnet will be increased. With the development of permanent magnet material production technology, adding a protective coating on the surface of the magnet can completely solve the disadvantage of poor corrosion resistance of the magnet.

[0004] Surface treatment of NdFeB magnets is one of the effective means to improve their corrosion resistance. Summary of the invention

[0005] The purpose of the present invention is to provide a manufacturing process for high-performance sintered NdFeB magnets to solve the following technical problems:

[0006] The existing alloying method achieves corrosion resistance of NdFeB magnets by adding alloying elements during the preparation process of NdFeB magnets. However, the intergranular phases formed inside the magnets by the addition of alloying elements are all non-magnetic phases, which causes the magnetic properties of the magnets to decrease.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A manufacturing process for a high-performance sintered NdFeB magnet comprises the following steps: using the sintered NdFeB magnet as a negative electrode material, placing it in an electrophoresis solution for electrophoresis treatment, coating the surface of the sintered NdFeB magnet with an anti-corrosion coating, and obtaining a high-performance sintered NdFeB magnet;

[0009] The method for preparing the electrophoresis solution comprises the following steps: mixing epoxy resin, additives and distilled water, and adjusting the pH to 5-6 to obtain the electrophoresis solution;

[0010] The preparation method of the additive comprises the following steps:

[0011] S1: Add nano-silicon dioxide and deionized water into a reaction kettle and disperse them evenly, add 3-chloropropyltrimethoxysilane ethanol solution, control the temperature at 70-80°C, keep warm and hydrolyze for 3-6 hours, wash, dry, crush and sieve to obtain component 1;

[0012] S2: Add 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water into a reaction bottle and disperse them evenly. Add sodium hydroxide and component 1 and control the temperature to 80-90°C. Keep the temperature for 3-6 hours. Add dilute sulfuric acid to terminate the reaction. Filter, wash and dry to obtain the additive.

[0013] As a further solution of the present invention: the content of 3-chloropropyltrimethoxysilane in the 3-chloropropyltrimethoxysilane ethanol solution is 0.1-0.15 g / mL; the pH value of the 3-chloropropyltrimethoxysilane ethanol solution is 4-5; the addition ratio of nano-silica: deionized water: 3-chloropropyltrimethoxysilane ethanol solution in S1 is 1 g: 10-50 mL: 2-5 mL.

[0014] As a further embodiment of the present invention: the mass ratio of 2-amino-5-mercapto-1,3,4-thiadiazole, deionized water, sodium hydroxide and component one in S2 is 1:30-60:0.5-0.8:1-2.

[0015] As a further solution of the present invention: the mass ratio of epoxy resin to distilled water is 4:5-8; and the additive is added in an amount of 5-20 g / L in the electrophoresis solution.

[0016] As a further solution of the present invention: during the electrophoresis treatment, the temperature of the electrophoresis liquid is controlled at 30-40°C.

[0017] As a further solution of the present invention: during the electrophoresis treatment, 304 stainless steel is used as the anode.

[0018] As a further solution of the present invention: during the electrophoresis treatment, the power supply voltage is 40-150V and the electrophoresis time is 15-150s.

[0019] As a further scheme of the present invention: the sintered NdFeB magnet needs to be pretreated before electrophoresis treatment; the specific steps of the pretreatment are: alkali washing, water washing, acid washing, water washing, ethanol washing, and drying; the specific steps of the alkali washing are: placing the magnet in a 3-5wt% sodium hydroxide solution for washing for 5-30s; the specific steps of the acid washing are: placing the magnet in a 3-5wt% nitric acid solution for washing for 5-30s.

[0020] As a further solution of the present invention: the sintered NdFeB magnet needs to be post-processed after electrophoresis treatment; the specific steps of the post-treatment are: washing the magnet with water, drying, curing at 160-210°C for 15-30 minutes, and cooling to obtain a high-performance sintered NdFeB magnet.

[0021] As a further embodiment of the present invention: the preparation method of sintered NdFeB magnet comprises the following steps:

[0022] A1: Mixing raw material powders according to a ratio to obtain raw material powder;

[0023] A2: Raw material powder is melted into alloy, cast into flakes, hydrogen crushed, and jet milled to obtain fine powder;

[0024] A3: The fine powder is mixed with AlN powder, dried, oriented in a magnetic field, and statically pressed to obtain a green body;

[0025] A4: The green body is vacuum sintered to obtain NdFeB sintered magnet.

[0026] As a further embodiment of the present invention, the raw material powder includes pure Fe, pure Pr, pure Nd, pure Cu, and boron iron alloy; the raw materials are in accordance with the following chemical formula (Pr 0.25 Nd 0.75 ) 30.6 Cu 0.15 Fe 67.25 The mass percentage of B1 is weighed; the boron iron alloy is Fe 80.6 B 19.4 (wt%)).

[0027] As a further solution of the present invention, the specific steps of melting the alloy are: placing a crucible containing raw material powder in a quick-setting furnace and evacuating the vacuum to 1×10-2 -3×10 -2 Pa, inject 0.01-0.03MPa argon gas, raise the temperature to 1250-1450℃, melt and obtain a molten liquid.

[0028] As a further solution of the present invention, the specific steps of casting are: passing the molten liquid through a copper roller to form an alloy casting sheet with a thickness of 0.05-1 mm, no α-Fe phase precipitation and uniform distribution of Nd-rich phase.

[0029] As a further solution of the present invention: the particle size of the fine powder is 2-5 μm.

[0030] As a further solution of the present invention: the fine powder is mixed with AlN powder by ball milling and dried to obtain a magnetic powder material; wherein the AlN powder accounts for 0.1-0.3wt% of the total mass of the magnetic powder material.

[0031] As a further solution of the present invention: the specific steps of magnetic field orientation are: orienting the magnetic powder in a 1.65T-2.0T magnetic field; the specific steps of static pressure forming are: isostatic pressing with oil cooling at 17MPa-200MPa for 30s to obtain a green body.

[0032] As a further solution of the present invention: the specific steps of vacuum sintering are: vacuum sintering at 1000-1050°C for 5-6.5h, cooling to 680-750°C and keeping warm for 1h, and then continuing to cool to obtain a NdFeB sintered magnet.

[0033] Beneficial effects of the present invention:

[0034] (1) The present application first uses 3-chloropropyltrimethoxysilane as a modifier to organically modify nano-silicon dioxide to obtain component one; and uses 2-amino-5-mercapto-1,3,4-thiadiazole to react with component one to graft thiadiazole groups and amino groups on the surface of silicon dioxide to obtain an additive; the present application also adds AlN powder as alloy particles during the preparation of sintered NdFeB magnets to prepare a new type of sintered NdFeB magnet; the present application uses the synergistic effect of the additive and AlN to effectively improve the adhesion strength between the coating and the magnet, giving the sintered NdFeB magnet excellent corrosion resistance without affecting the magnetic properties of the magnet itself.

[0035] This application utilizes 3-chloropropyltrimethoxysilane and 2-amino-5-mercapto-1,3,4-thiadiazole to graft on the surface of silica, so that functional groups such as amino groups and thiadiazole groups are grafted on the surface of nano-silica. As the additive is added to the electrophoretic liquid, the electrophoretic liquid is used to perform electrochemical deposition on the surface of the magnet to form a uniform, flat, and defect-free coating on the surface of the magnet, which effectively and tightly wraps the substrate, isolates the corrosive medium, and effectively prevents the substrate from contacting the corrosive medium and chemically corroding; the epoxy resin and additives in the coating have strong chemical stability and good corrosion resistance in acid and Cl- environments. The interface bonding between the additive and the epoxy resin is good, and no interface corrosion will occur; the epoxy resin and silica have low electrical conductivity, which effectively hinders the electronic conduction and electronic exchange on the surface of the material and prevents the material from electrochemical corrosion.

[0036] (2) The additives of this application are organically cross-linked with epoxy resin through functional groups and are uniformly embedded in the epoxy resin molecular chains. Silicon dioxide, as the cross-linking point of the epoxy resin molecular chains, has strong interactions and forms a strong chemical force. It not only hinders the diffusion and penetration of small molecules produced when the molecular chains are cracked when the epoxy resin is degraded at high temperature, but also greatly increases the thermal decomposition temperature of the epoxy resin coating. It also effectively hinders the movement of molecular chains in the epoxy resin coating, reduces the porosity of the coating, increases the density of the coating, and prolongs the corrosion channel for the corrosive solution to penetrate into the magnet. This application organically combines the additives with the epoxy resin through chemical bonds, effectively avoiding the problem of directly adding inorganic particles, resulting in particle agglomeration, increased coating roughness, and further increasing the contact area between the coating and the corrosive electrolyte solution, and reducing the corrosion resistance of the coating.

[0037] (3) The present application adds additives to the electrophoresis solution. During electrophoresis, the additives are preferentially deposited on the substrate surface, and the organic matter is enriched at the interface between the coating and the metal substrate, thereby improving the bonding force between the coating and the substrate, thereby further improving the protective performance of the coating. The additives are tightly bonded to the substrate surface, and the corrosion products produced by early pitting corrosion are firmly covered under the interface layer and are not easy to move. In addition, the functional groups such as thiadiazole groups on the surface of the additives themselves allow the original pitting corrosion to have enough time to passivate again, so that the corrosion is suppressed and the corrosion resistance is greatly improved.

[0038] (4) The present application utilizes additives and epoxy resin to reduce the diffusion rate of water in the epoxy resin coating, increase the hydrophobicity of the coating interface, and improve the corrosion resistance of the epoxy coating; effectively solve the problem that during the use of the magnet, the polar Si-OH of the silane coupling agent forms hydrogen bonds with water, adsorbs a large amount of water, and the Nd-rich region generates Nd+3H2O→Nd(OH)3+3H + , the H generated by the reaction +The atoms penetrate into the grain boundaries and further react with the Nd-rich, causing further corrosion of the grain boundaries, causing the coating to expand and bubble, resulting in a decrease in the barrier performance of the coating. The present application forms a dense coating on the surface of the magnet to effectively solve the problem of Nd+3O2→2Nd2O3, Nd2Fe 14 Phase B will decompose to form Fe and Nd2O3. Further oxidation will produce products such as ferric oxide, leading to a decrease in magnetic properties. DETAILED DESCRIPTION

[0039] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0040] Example 1 The preparation method of sintered NdFeB magnet comprises the following steps:

[0041] A1: According to the chemical formula (Pr 0.25 Nd 0.75 ) 30.6 Cu 0.15 Fe 67.25 B1 mass percentage added pure Fe, pure Pr, pure Nd, pure Cu, boron iron alloy (Fe 80.6 B 19.4 (wt%)) to obtain raw material powder;

[0042] A2: The raw material powder is smelted alloy. The specific steps of smelting alloy are as follows: placing the crucible containing the raw material powder in a quick-setting furnace and evacuating the vacuum to 3×10 -2 Pa, inject 0.03MPa argon gas, heat to 1450℃, melt, and obtain molten liquid;

[0043] A3: The molten metal is passed through a copper roller to form an alloy sheet with a thickness of 0.05 mm, no α-Fe phase precipitation and uniform distribution of Nd-rich phase;

[0044] A4: The alloy flakes were subjected to hydrogen crushing and jet milling to obtain fine powder with a particle size of 5 μm;

[0045] A5: The fine powder is mixed with AlN powder with a particle size of 20 nm by ball milling and dried to obtain magnetic powder material; wherein the AlN powder accounts for 0.3wt% of the total mass of the magnetic powder material;

[0046] A6: Orient the magnetic powder in a 1.65T magnetic field and hold the pressure at 100MPa oil cooling isostatic pressing for 30s to obtain a green body;

[0047] A7: Vacuum sintering at 1050℃ for 6h, cooling to 750℃ and keeping for 1h, then continuing cooling to obtain NdFeB sintered magnet.

[0048] Example 2 The preparation method of the additive comprises the following steps:

[0049] S1: After mixing 3-chloropropyltrimethoxysilane with anhydrous ethanol, glacial acetic acid is added to adjust the pH to 4 to obtain a 3-chloropropyltrimethoxysilane ethanol solution with a 3-chloropropyltrimethoxysilane concentration of 0.1 g / mL;

[0050] S2: 1 g of nano-silicon dioxide and 10 mL of deionized water were added to a reaction kettle and dispersed evenly, 2 mL of 3-chloropropyltrimethoxysilane ethanol solution was added, the temperature was controlled at 70°C, and the mixture was kept warm for hydrolysis for 3 h, washed, dried, crushed, and passed through a 400-mesh sieve to obtain component 1;

[0051] S3: Add 1 g of 2-amino-5-mercapto-1,3,4-thiadiazole and 30 mL of deionized water into a reaction bottle and disperse evenly. Add 0.5 g of sodium hydroxide and 2 g of component 1 and control the temperature to 80°C. Keep the temperature for 3 h. Add dilute sulfuric acid to terminate the reaction. Filter, wash and dry to obtain the additive.

[0052] Example 3 The preparation method of the additive comprises the following steps:

[0053] S1: After mixing 3-chloropropyltrimethoxysilane with anhydrous ethanol, glacial acetic acid is added to adjust the pH to 4 to obtain a 3-chloropropyltrimethoxysilane ethanol solution with a 3-chloropropyltrimethoxysilane concentration of 0.1 g / mL;

[0054] S2: 1 g of nano-silicon dioxide and 30 mL of deionized water were added to a reaction kettle and dispersed evenly, 3.5 mL of 3-chloropropyltrimethoxysilane ethanol solution was added, the temperature was controlled at 75°C, and the mixture was kept warm for 4 h for hydrolysis, washed, dried, crushed, and passed through a 400-mesh sieve to obtain component 1;

[0055] S3: Add 1 g of 2-amino-5-mercapto-1,3,4-thiadiazole and 45 mL of deionized water into a reaction bottle and disperse evenly. Add 0.6 g of sodium hydroxide and 2 g of component 1 and control the temperature to 85°C. Keep the temperature for 6 h. Add dilute sulfuric acid to terminate the reaction. Filter, wash and dry to obtain the additive.

[0056] Example 4 The preparation method of the additive comprises the following steps:

[0057] S1: After mixing 3-chloropropyltrimethoxysilane with anhydrous ethanol, glacial acetic acid is added to adjust the pH to 4 to obtain a 3-chloropropyltrimethoxysilane ethanol solution with a 3-chloropropyltrimethoxysilane concentration of 0.1 g / mL;

[0058] S2: 1 g of nano-silicon dioxide and 50 mL of deionized water were added to a reaction kettle and dispersed evenly, 5 mL of 3-chloropropyltrimethoxysilane ethanol solution was added, the temperature was controlled at 80°C, and the hydrolysis was carried out for 6 hours, and then washed, dried, crushed, and passed through a 400-mesh sieve to obtain component 1;

[0059] S3: Add 1 g of 2-amino-5-mercapto-1,3,4-thiadiazole and 60 mL of deionized water into a reaction bottle and disperse evenly. Add 0.8 g of sodium hydroxide and 2 g of component 1 and control the temperature to 90°C. Keep the temperature for 6 h. Add dilute sulfuric acid dropwise to terminate the reaction. Filter, wash and dry to obtain the additive.

[0060] Embodiment 5 A process for manufacturing a high performance sintered NdFeB magnet comprises the following steps:

[0061] B1: preparing electrophoresis liquid: 4 g of epoxy resin (bisphenol A epoxy resin, epoxy group content 1810-2000 mmol / kg), the additive prepared in Example 2, and 8 g of distilled water were mixed, and acetic acid was added to adjust the pH to 5 to obtain an electrophoresis liquid, wherein the amount of the additive added to the electrophoresis liquid was 10 g / L;

[0062] B2: Pretreatment of sintered NdFeB magnets: The magnets prepared in Example 1 were placed in a 4wt% sodium hydroxide solution for cleaning for 5s, washed with water, placed in a 4wt% nitric acid solution for cleaning for 10s, washed with water, washed with ethanol, and dried to obtain pretreated sintered NdFeB magnets;

[0063] B3: Electrophoresis treatment: The temperature of the electrophoresis solution is controlled at 35°C. The pretreated sintered NdFeB magnet is used as the negative electrode material and 304 stainless steel is used as the anode. The pretreated NdFeB magnet is placed in the electrophoresis solution for electrophoresis treatment. The power supply voltage is 120V and the electrophoresis time is 15s. The surface of the sintered NdFeB magnet is coated with an anti-corrosion coating to obtain a sintered NdFeB magnet precursor.

[0064] B4: Post-treatment of sintered NdFeB magnet precursor: The sintered NdFeB magnet precursor is washed with water, dried, cured at 210°C for 15 minutes, and cooled to obtain a high-performance sintered NdFeB magnet.

[0065] Embodiment 6 A process for manufacturing a high performance sintered NdFeB magnet comprises the following steps:

[0066] B1: preparing electrophoresis liquid: 4 g of epoxy resin (bisphenol A epoxy resin, epoxy group content 1810-2000 mmol / kg), the additive prepared in Example 3, and 8 g of distilled water were mixed, and acetic acid was added to adjust the pH to 5 to obtain an electrophoresis liquid, wherein the amount of the additive added to the electrophoresis liquid was 10 g / L;

[0067] B2: Pretreatment of sintered NdFeB magnets: The magnets prepared in Example 1 were placed in a 4wt% sodium hydroxide solution for cleaning for 5s, washed with water, placed in a 4wt% nitric acid solution for cleaning for 10s, washed with water, washed with ethanol, and dried to obtain pretreated sintered NdFeB magnets;

[0068] B3: Electrophoresis treatment: The temperature of the electrophoresis solution is controlled at 35°C. The pretreated sintered NdFeB magnet is used as the negative electrode material and 304 stainless steel is used as the anode. The pretreated NdFeB magnet is placed in the electrophoresis solution for electrophoresis treatment. The power supply voltage is 120V and the electrophoresis time is 15s. The surface of the sintered NdFeB magnet is coated with an anti-corrosion coating to obtain a sintered NdFeB magnet precursor.

[0069] B4: Post-treatment of sintered NdFeB magnet precursor: The sintered NdFeB magnet precursor is washed with water, dried, cured at 210°C for 15 minutes, and cooled to obtain a high-performance sintered NdFeB magnet.

[0070] Embodiment 7 A process for manufacturing a high performance sintered NdFeB magnet comprises the following steps:

[0071] B1: preparing electrophoresis liquid: 4 g of epoxy resin (bisphenol A epoxy resin, epoxy group content 1810-2000 mmol / kg), the additive prepared in Example 4, and 8 g of distilled water were mixed, and acetic acid was added to adjust the pH to 5 to obtain an electrophoresis liquid, wherein the amount of the additive added to the electrophoresis liquid was 10 g / L;

[0072] B2: Pretreatment of sintered NdFeB magnets: The magnets prepared in Example 1 were placed in a 4wt% sodium hydroxide solution for cleaning for 5s, washed with water, placed in a 4wt% nitric acid solution for cleaning for 10s, washed with water, washed with ethanol, and dried to obtain pretreated sintered NdFeB magnets;

[0073] B3: Electrophoresis treatment: The temperature of the electrophoresis solution is controlled at 35°C. The pretreated sintered NdFeB magnet is used as the negative electrode material and 304 stainless steel is used as the anode. The pretreated NdFeB magnet is placed in the electrophoresis solution for electrophoresis treatment. The power supply voltage is 120V and the electrophoresis time is 15s. The surface of the sintered NdFeB magnet is coated with an anti-corrosion coating to obtain a sintered NdFeB magnet precursor.

[0074] B4: Post-treatment of sintered NdFeB magnet precursor: The sintered NdFeB magnet precursor is washed with water, dried, cured at 210°C for 15 minutes, and cooled to obtain a high-performance sintered NdFeB magnet.

[0075] Comparative Example 1 The preparation method of a sintered NdFeB magnet comprises the following steps:

[0076] A1: According to the chemical formula (Pr 0.25 Nd 0.75 ) 30.6 Cu 0.15 Fe 67.25B1 mass percentage added pure Fe, pure Pr, pure Nd, pure Cu, boron iron alloy (Fe 80.6 B 19.4 (wt%)) to obtain raw material powder;

[0077] A2: The raw material powder is smelted alloy. The specific steps of smelting alloy are as follows: placing the crucible containing the raw material powder in a quick-setting furnace and evacuating the vacuum to 3×10 -2 Pa, inject 0.03MPa argon gas, heat to 1450℃, melt, and obtain molten liquid;

[0078] A3: The molten metal is passed through a copper roller to form an alloy sheet with a thickness of 0.05 mm, no α-Fe phase precipitation and uniform distribution of Nd-rich phase;

[0079] A4: The alloy flakes were subjected to hydrogen crushing and jet milling to obtain fine powder with a particle size of 5 μm;

[0080] A5: Orient the magnetic powder in a 1.65T magnetic field and hold the pressure at 100MPa oil cooling isostatic pressure for 30s to obtain a green body;

[0081] A6: Vacuum sintering at 1050℃ for 6h, cooling to 750℃ and keeping for 1h, then continuing cooling to obtain NdFeB sintered magnet.

[0082] Comparative Example 2 The preparation method of the additive comprises the following steps:

[0083] S1: After mixing 3-chloropropyltrimethoxysilane with anhydrous ethanol, glacial acetic acid is added to adjust the pH to 4 to obtain a 3-chloropropyltrimethoxysilane ethanol solution with a 3-chloropropyltrimethoxysilane concentration of 0.1 g / mL;

[0084] S2: Add 1 g of nano-silica and 10 mL of deionized water into a reaction kettle and disperse them evenly, add 2 mL of 3-chloropropyltrimethoxysilane ethanol solution, control the temperature at 70°C, keep the temperature for hydrolysis for 3 hours, wash, dry, crush, and pass through a 400-mesh sieve to obtain an additive.

[0085] Comparative Example 3 The preparation method of the additive comprises the following steps:

[0086] S1: After 3-aminopropyltriethoxysilane and anhydrous ethanol are mixed, glacial acetic acid is added to adjust the pH to 4 to obtain a 3-aminopropyltriethoxysilane ethanol solution with a 3-aminopropyltriethoxysilane concentration of 0.1 g / mL;

[0087] S2: 1 g of nano-silicon dioxide and 10 mL of deionized water were added to a reaction kettle and dispersed evenly, 2 mL of 3-aminopropyltriethoxysilane ethanol solution was added, the temperature was controlled at 70°C, and the mixture was kept warm for hydrolysis for 3 h, washed, dried, crushed, and passed through a 400-mesh sieve to obtain component 1;

[0088] S3: 1 g of 2-amino-5-mercapto-1,3,4-thiadiazole and 2 g of component 1 are mixed to obtain an additive.

[0089] Comparative Example 4

[0090] Compared with Example 5, Comparative Example 4 only replaces the additive prepared in Example 2 used in Example 5 with an equal amount of the additive prepared in Comparative Example 2, and the remaining components and preparation method are completely consistent with Example 5.

[0091] Comparative Example 5

[0092] Compared with Example 5, Comparative Example 5 only replaces the additive prepared in Example 2 used in Example 5 with an equal amount of the additive prepared in Comparative Example 3, and the remaining components and preparation method are completely consistent with those of Example 5.

[0093] Comparative Example 6

[0094] Compared with Example 5, Comparative Example 6 only replaces the NdFeB sintered magnet prepared in Example 1 used in Example 5 with the NdFeB sintered magnet prepared in Comparative Example 1, and the remaining components and preparation method are completely consistent with those of Example 5.

[0095] Performance Testing

[0096] (1) Coating adhesion: The test was conducted in accordance with GB / T 9286-1998 “Scratch test for paint and varnish films”. The test results are shown in Table 1;

[0097] (2) Hardness: HVS-1000 microhardness tester was used, with a load of 200 g and a loading time of 10 s. The test results are shown in Table 1.

[0098] (3) Electrochemical performance: A CHI660D electrochemical workstation equipped with Swiss Metrohm China Co., Ltd. was used. A three-electrode working system was used. The steel sheets coated with the anti-corrosion coatings of Examples 5-7 and Comparative Examples 4-5 were used as working electrodes (area 10 mm × 10 mm), and saturated calomel electrode (SCE) was used as reference electrode (area 1 cm 2 The platinum mesh was used as the auxiliary electrode; the sample was sealed with HY914 glue, the corrosion medium was 3wt% sodium chloride solution, and the open circuit voltage was used as the starting voltage during EIS measurement, and the frequency was 0.01-10 5 Hz, the interference signal is 10mV, and the test temperature is room temperature; the changes in the corrosion current density and corrosion potential of the test sample are tested, and the positive and negative polarization curves are made through E-LogI. The intersection of the two lines is taken as the corrosion potential (Eeorr), and the intersection of the two curve tangents is taken as the corrosion current (Ieorr). The test results are shown in Table 1;

[0099] Table 1: Statistical table of physical and chemical properties of corrosion-resistant coatings of Examples 5-7 and Comparative Examples 4-6

[0100]

[0101] As can be seen from Table 1, the coating prepared in the present application is coated on the surface of the magnet, and the anti-corrosion coating prepared by the present application has the characteristics of high hardness and good adhesion performance. In addition, the present application effectively increases the corrosion potential and reduces the corrosion current by coating the anti-corrosion coating on the surface of the magnet by the method of electrodeposition, thereby giving the magnet excellent corrosion resistance.

[0102] (4) Neutral smoke test: According to GB / T 10125-2012 "Artificial atmosphere corrosion test salt spray test", the test is carried out using a TMHW-90 programmable salt spray test machine. The test chamber temperature is (35±2)℃, the humidity is greater than 95%, and the fog drop is 1-2mL / (h·cm 2 ), NaCl solution concentration is 50g / L. When the first corrosion product observed by naked eyes appears on the surface of the test product, the time is terminated. The corresponding test time at this time is the neutral salt spray resistance time of the product. The test results are shown in Table 2;

[0103] (5) High temperature and high pressure aging accelerated test (PCT): The test was conducted in an EHS-211ESPEC hot and cold shock test chamber with a temperature of 120°C, a humidity of 100%, and a pressure of 2 atm. When the first corrosion product observed by the naked eye appeared on the surface of the test product, the test time was terminated. The corresponding test time at this time was the PCT resistance time of the product. The test results are shown in Table 2.

[0104] (6) Humidity test: the test chamber temperature is 80℃ and the humidity is 90% (deionized water with a pH of 6.7-7.2 is used to provide humidity). When the first corrosion product observed by the naked eye appears on the surface of the test product, the test time is terminated. The corresponding test time at this time is the humidity and heat resistance time of the product. The test results are shown in Table 2.

[0105] (7) Hot and cold test: The test was conducted in a TSE-12-AESPEC hot and cold shock test chamber. The test chamber was subjected to a low temperature of -40°C for 3 hours and a high temperature of 150°C for 3 hours. After 500 hot and cold cycle shocks, the coating surface was considered qualified if there were no obvious defects such as bubbles (bulges), peeling, or powdering. The test results are shown in Table 2.

[0106] Table 2: Statistical table of coating performance test data for Examples 5-7 and Comparative Examples 4-6

[0107]

[0108] It can be seen from Table 2 that the coating of the present application has a good composite effect with the magnet, the coating has good weather resistance, and gives the magnet excellent corrosion resistance.

[0109] (8) The magnetic properties of the samples prepared in Examples 5-7 and Comparative Examples 4-5 were measured using a magnetic property tester. The test results are shown in Table 3.

[0110] Table 3: Statistical table of magnetic properties test data of Examples 5-7 and Comparative Examples 4-5

[0111]

[0112] It can be seen from Table 3 that the coating prepared in the present application has little effect on the magnetic properties of the sintered NdFeB magnet itself.

[0113] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A manufacturing process for high performance sintered NdFeB magnets, characterized in that: The method comprises the following steps: using a sintered NdFeB magnet as a negative electrode material, placing the magnet in an electrophoresis solution for electrophoresis treatment, coating the surface of the sintered NdFeB magnet with an anti-corrosion coating, and obtaining a high-performance sintered NdFeB magnet; The method for preparing the electrophoresis solution comprises the following steps: mixing epoxy resin, additives and distilled water, and adjusting the pH to 5-6 to obtain the electrophoresis solution; The preparation method of the additive comprises the following steps: S1: Add nano-silicon dioxide and deionized water into a reaction kettle and disperse them evenly, add 3-chloropropyltrimethoxysilane ethanol solution, control the temperature at 70-80°C, keep warm and hydrolyze for 3-6 hours, wash, dry, crush and sieve to obtain component 1; S2: Add 2-amino-5-mercapto-1,3,4-thiadiazole and deionized water into a reaction bottle and disperse them evenly, add sodium hydroxide and component 1, control the temperature to 80-90°C, keep the temperature for 3-6 hours, dropwise add dilute sulfuric acid to terminate the reaction, filter, wash and dry to obtain the additive; The content of 3-chloropropyltrimethoxysilane in the 3-chloropropyltrimethoxysilane ethanol solution is 0.1-0.15 g / mL; the pH of the 3-chloropropyltrimethoxysilane ethanol solution is 4-5; the addition ratio of nano-silica: deionized water: 3-chloropropyltrimethoxysilane ethanol solution in S1 is 1 g: 10-50 mL: 2-5 mL; The mass ratio of 2-amino-5-mercapto-1,3,4-thiadiazole, deionized water, sodium hydroxide and component one in S2 is 1:30-60:0.5-0.8:1-2.

2. The manufacturing process of a high performance sintered NdFeB magnet according to claim 1, characterized in that: The mass ratio of the epoxy resin to distilled water is 4:5-8; the amount of the additive added to the electrophoresis liquid is 5-20 g / L.

3. The manufacturing process of a high performance sintered NdFeB magnet according to claim 1, characterized in that: During the electrophoresis treatment, the temperature of the electrophoresis solution is controlled at 30-40°C.

4. The manufacturing process of a high performance sintered NdFeB magnet according to claim 1, characterized in that: During the electrophoresis treatment, 304 stainless steel is used as the anode; the power supply voltage is 40-150V, and the electrophoresis time is 15-150s.

5. The manufacturing process of a high performance sintered NdFeB magnet according to claim 1, characterized in that: The sintered NdFeB magnet needs to be pretreated before electrophoresis treatment; the specific steps of the pretreatment are: alkali washing, water washing, acid washing, water washing, ethanol washing, and drying; the specific steps of the alkali washing are: placing the magnet in a 3-5wt% sodium hydroxide solution for washing for 5-30s; the specific steps of the acid washing are: placing the magnet in a 3-5wt% nitric acid solution for washing for 5-30s.

6. The manufacturing process of a high performance sintered NdFeB magnet according to claim 1, characterized in that: The sintered NdFeB magnet needs to be post-processed after the electrophoresis treatment; the specific steps of the post-processing are: washing the magnet with water, drying it, curing it at 160-210° C. for 15-30 minutes, and cooling it to obtain a high-performance sintered NdFeB magnet.

7. The manufacturing process of a high performance sintered NdFeB magnet according to claim 1, characterized in that: The preparation method of sintered NdFeB magnets comprises the following steps: A1: Mixing raw material powders according to a ratio to obtain raw material powder; A2: Raw material powder is melted into alloy, cast into flakes, hydrogen crushed, and jet milled to obtain fine powder; A3: The fine powder is mixed with AlN powder, dried, oriented in a magnetic field, and statically pressed to obtain a green body; A4: The green body is vacuum sintered to obtain NdFeB sintered magnet.

Citation Information

Patent Citations

  • Method for preparing anti-corrosion wear-resisting sintered Nd-Fe-B magnets

    CN103996525A

  • SMC wallboard waterproof nano coating material

    CN116948498A